Respuesta :

Answer:

Step-by-step explanation:

Expand:

-1(x^2-6x+9)+4=-x^2+6x-9 + 4 =  -x^2 + 6x - 5

Answer:

See Below.

Step-by-step explanation:

We want to prove that:

[tex]-(x-3)^2+4=-x^2+6x-5[/tex]

So, let’s expand the left side. This gives us:

[tex]=-(x-3)(x-3)+4[/tex]

Distribute:

[tex]=-(x^2-3x-3x+9)+4[/tex]

Simplify:

[tex]=-(x^2-6x+9)+4[/tex]

Distribute:

[tex]=-x^2+6x-9+4[/tex]

Simplify:

[tex]=-x^2+6x-5[/tex]

Hence:

[tex]-(x-3)^2+4\stackrel{\checkmark}{=}-x^2+6x-5[/tex]

ACCESS MORE